Microbial Testing of Raw Bread - Stará, Ivana; Bugáňová, Veronika; Brožková, Iveta; Pejchalová, Marcela; Červenka, Libor (Garmond Nitra, 2024)
Raw food diet, raw foodism (rawism) or vitarianism is a diet based on consuming mainly or even exclusively uncooked food up to a temperature of 42 °C. Raw food is rich in fibre, minerals, antioxidants and vitamins. Mixing, juicing, soaking, sprouting and fermenting are integral in raw diets The only heating allowed is with a dehydrator. However, uncooked food is at risk of bacterial contamination or even food poisoning. Microbial representation was determined for raw bread prepared according to a recipe for alternative ways of eating. Mold was visible on the bread surface after three days of storage at room temperature. We also investigated the influence of the microbial representation and the amount of antioxidants in the prepared raw bread depending on the presence of Lactobacillus acidophilus and Fusarium. The effect of Lactobacillus acidophilus on the growth and multiplication of Fusarium langsethiae in raw bread was not confirmed. But the effect of Lactobacillus acidophilus on the production of mycotoxins was established (T-2, HT-2, neosolaniol, diacetoxyscirpenol). According to our results, this bread should therefore be consumed immediately and not stored.
Mikrobiální testování raw chleba
Keywords: foodborne illness; foodborne intoxication; alternative diet; raw bread; alimentární onemocnění; alternativní směry stravování; raw chléb